Application of Concrete and Demolition Waste as CO2 Sorbent in Chemical Looping Gasification of Biomass - Moghtaderi, B.; Zanganeh, J.; Shah, K.; Wu, Hongwei (American Chemical Society, 2012)
This paper summarizes the results of an experimental investigation into sorbent chemical looping gasification (SCLG) of biomass for the production of high-purity hydrogen and in situ capture of the resulting CO2. The key innovation was the use of concrete and demolition waste (CDW) as the source of CO2 sorbent. A comprehensive series of thermogravimetric analysis (TGA) experiments was carried out over a range of temperatures between 650 and 900 °C and pressures up to 20 atm to benchmark the CO2 capture efficiency of CDW against conventional lime-based sorbents [e.g., calcined limestone (CL) and hydrated Portland cement (HPC)]. Effects of controlling parameters, such as the Ca/C ratio, steam/carbon (S/C) ratio, steam partial pressure, and total pressure, on the gas yield, gas composition, and CO2 capture efficiency were thoroughly examined. Experimental results confirmed that CO2 capture efficiencies as high as 56.4% and high-grade hydrogen production can be achieved when CDW is used as a sorbent. These results combined with the high mechanical strength, durability, and low cost make CDW an attractive sorbent for chemical looping gasification of carbonaceous solid fuels, particularly biomass.